OPTIMIZING INCISION DEPTH IN SUNNAH CUPPING THERAPY FOR SAFETY AND THERAPEUTIC EFFICACY - Isdianto, Andik; Fitrianti, Novariza (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to evaluate the impact of incision depth in Sunnah cupping therapy on safety and therapeutic efficacy, with a focus on identifying the optimal incision depth that minimizes risks while maximizing therapeutic benefits. The method used is a literature review, gathering data from scientific databases such as PubMed, Scopus, and Google Scholar using keywords related to cupping therapy, incision depth, and dermatological aspects. The findings reveal that an incision depth of 0.5 mm to 1 mm in the dermis layer not only avoids damage to the deeper hypodermis but is also sufficient for the effective extraction of stagnant blood. This very light incision provides advantages in enhancing blood circulation and facilitating the extraction of stagnant blood necessary in cupping therapy. This approach, involving extremely light incisions, cannot be considered invasive and is highly suitable for enhancing therapy efficacy without compromising patient safety. Further discussion in the study highlights that with the correct incision technique, cupping therapy can become safer and more effective, encouraging significant improvements in immune response and tissue regeneration. The conclusion of this study underscores the importance of standardizing procedures and adequate training for cupping practitioners to ensure safe and effective practices. Further research is recommended to strengthen the evidence related to the effectiveness and safety of cupping therapy and to develop more detailed standard protocols.